The Influence of Organizational Commitment on Employee Performance in Multinational Companies - Juan Sergio Sihotang (Patua : Journal of Business Administration and Management, 2024)
This study aims to analyze the influence of organizational commitment on employee performance in multinational companies. The approach used in this study is quantitative with a survey method. Data were collected by distributing questionnaires to 120 respondents who were permanent employees with a minimum of one year of service. Data analysis techniques used included validity testing, reliability testing, descriptive analysis, and simple linear regression analysis. The results of the study indicate that organizational commitment has a positive and significant influence on employee performance. This is evidenced by a significance value of 0.000 < 0.05 and a regression coefficient that indicates a positive relationship between the two variables. In addition, the coefficient of determination (R²) value of 0.62 indicates that organizational commitment is able to explain 62% of the variation in employee performance, while the remainder is influenced by other factors outside the study. These findings indicate that the higher the level of organizational commitment, whether in the affective, sustainable, or normative dimensions, the higher the performance produced by employees. Therefore, multinational companies are advised to increase organizational commitment by strengthening work culture, providing rewards, and developing employee careers.